A modified graphite negative electrode material for lithium ion battery and its preparation method and application

By adopting a modified graphite negative electrode material with a core-shell structure, the stability and ion transmission efficiency of the SEI film are improved by using carbon materials with high electronegative non-metal/metal heteroatom co-doped carbon materials, the efficiency reduction problem caused by the formation of SEI film in lithium-ion batteries is solved, and efficient battery performance improvement is achieved.

CN119361663BActive Publication Date: 2025-04-04INST OF ENERGY HEFEI COMPREHENSIVE NAT SCI CENT (ANHUI ENERGY LAB)

Patent Information

Application Number
CN202411919619.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The solid electrolyte interface film (SEI film) formed by the graphite anode material of existing lithium-ion batteries during the first charging process leads to a reduction in the first round of Coulomb efficiency, and the lack of inorganic lithium-containing components with high ionic conductivity and high Young's modulus in the SEI film, affecting interface stability and ion transport efficiency.

Method used

A modified graphite negative electrode material with a core-shell structure is adopted, with graphite particles as the core, and the outer shell is composed of carbon material co-doped with high electronegative non-metal/metal heteroatoms. Doped metal ions are used as the core center of LiF to form a uniform alkali metal fluorine salt, improving the stability and ion transport efficiency of the SEI film.

Benefits of technology

The first-round Coulomb efficiency, cycle life and high-current charging and discharging performance of lithium-ion batteries are significantly improved, forming a more stable and dense SEI film, reducing irreversible lithium loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361663B_ABST
    Figure CN119361663B_ABST
Patent Text Reader

Abstract

The present invention discloses a modified graphite negative electrode material for lithium ion batteries and its preparation method and application. The present invention belongs to the field of battery technology. The negative electrode material is a core-shell structure, the internal core is graphite particles, and the external shell is a carbon material co-doped with highly electronegative non-metallic / metallic heteroatoms such as N, O, and F, wherein the weight ratio of the shell part doped carbon to the graphite is X, 2%≦X≦20%. Compared with the existing process, the negative electrode material can form a more stable, dense, continuous and high-ionic conductivity fluoride-rich SEI film, which can effectively avoid the breakage and loss of the SEI film in the later charging and discharging process, and can significantly improve the first-round coulomb efficiency of the negative electrode material while significantly improving the cycle life and high-current charging and discharging performance of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a modified graphite negative electrode material for a lithium ion battery, and a preparation method and application thereof. Background Art

[0002] With the rapid development of smart terminals, new energy vehicles and large-scale energy storage, the demand for lithium-ion batteries, as their core power source, continues to rise. In order to meet the needs of different application scenarios, lithium-ion batteries are developing in the direction of high energy density, high power density, low cost and high safety. These technological breakthroughs will further expand the application scope of lithium-ion batteries.

[0003] In lithium-ion battery systems, negative electrode materials are one of the key factors that determine their overall performance. At present, commercial lithium-ion batteries mainly use carbon materials as negative electrodes, among which graphite materials have become the most representative negative electrode materials due to their good conductivity, high crystallinity, high theoretical lithium insertion capacity (372mAh / g), stable layered structure, suitable charge and discharge voltage platform and low cost.

[0004] However, the graphite negative electrode in the prior art still has the following technical problems: Since the lithium insertion potential of the graphite negative electrode (about 0.2V vs. Li / Li+) is usually lower than the decomposition potential of the organic electrolyte, a solid electrolyte interface film (SEI film) will inevitably form on the surface of the graphite negative electrode during the first charging process, resulting in a decrease in the first round of coulombic efficiency. Secondly, although the SEI film is composed of organic and inorganic components (such as lithium carbonate, lithium fluoride, etc.), in the traditional carbonate-based electrolyte system, the SEI film formed is often rich in organic components, which leads to an increase in the battery interface impedance, which seriously restricts the performance of the battery.

[0005] Specifically, the above technology has the following defects: First, the formation process of the SEI film consumes a large amount of electrolyte, resulting in a significant decrease in the first-round coulombic efficiency of the battery; second, in the subsequent charge and discharge cycles, the SEI film will undergo continuous damage and reconstruction, accelerating the battery capacity decay; third, the conventional SEI film lacks inorganic lithium-containing components (such as LiF) with high ionic conductivity and high Young's modulus, which affects the interface ion transport kinetics and mechanical stability.

[0006] In view of this, it is urgent to develop a new method for modifying graphite negative electrodes to solve the following technical problems: first, how to promote uniform film formation of SEI film and improve the first-round coulombic efficiency through optimized design; second, how to increase the content of inorganic lithium-containing components (especially LiF) in SEI film to improve interface stability and ion transfer efficiency; third, how to achieve the above technical goals through a simple, easy and low-cost process route to ensure industrial feasibility.

[0007] The purpose of the present invention is to overcome the above-mentioned deficiencies in the prior art and to provide a method for modifying a graphite negative electrode that can simultaneously achieve high cycle stability, excellent power characteristics and high first-round coulombic efficiency. Summary of the invention

[0008] In view of the technical defects of low first-round coulombic efficiency, reduced capacity under high-current charge and discharge, and poor material stability of lithium-ion battery graphite negative electrode materials prepared by existing processes mentioned in the background technology, the purpose of the present invention is to provide a lithium-ion battery modified graphite negative electrode material and a preparation method and application thereof, aiming to improve the wettability of the negative electrode material, the film formation stability of the SEI film and the content of the inorganic component LiF, while solving the problems of low first-round coulombic efficiency of lithium-ion batteries, reduced energy density under high-power charge and discharge conditions, and poor cycle stability, thereby improving the comprehensive application performance of lithium-ion batteries.

[0009] In the first aspect, the present invention proposes a modified graphite negative electrode material for a lithium ion battery, wherein the negative electrode material has a core-shell structure, wherein the internal core is graphite particles, and the external shell is a carbon material co-doped with highly electronegative non-metal / metal heteroatoms such as N, O, and F, wherein the weight ratio of the carbon doped in the shell part to the graphite is X, 2%≦X≦20%, preferably 5%≦X≦15%.

[0010] In the above technical solution, the metal ions uniformly doped in the carbon shell can become the nucleation center of LiF during the first film formation process, forming a uniform alkali metal fluoride salt in the SEI, which helps to form a thin and dense SEI film and improve the Young's modulus and ion migration rate of the SEI film. Highly electronegative non-metals such as N, O, and F in the carbon shell will increase the polarity of the carbon shell, improve the wettability of the electrolyte, and then increase the interfacial migration rate of lithium ions and the subsequent high current charge and discharge performance. The uniform carbon shell coated on the graphite surface forms a synergistic effect with the doped metal and non-metal, which helps to form a more stable SEI film and reduce irreversible lithium loss.

[0011] In the above technical solution, the non-metallic heteroatom is any two or more of N, O, F, etc. The carbon shell layer doped with at least two or more of the above non-metallic heteroatoms can significantly improve the surface wettability of the negative electrode material, which helps to form a uniform and smooth SEI film on the one hand, and on the other hand can improve the interfacial transmission efficiency of lithium ions, thereby improving the charge and discharge performance of lithium-ion batteries under high current.

[0012] In the above technical solution, the weight ratio of the non-metallic heteroatom to graphite is 0.5-5%, preferably 1-3%, which can effectively improve the surface wettability of the negative electrode material. On the one hand, it helps to form a uniform and smooth SEI film, and on the other hand, it can improve the interfacial transmission efficiency of lithium ions, thereby improving the charge and discharge performance of lithium-ion batteries under high current.

[0013] In the above technical scheme, the metal heteroatom is any one or more of Bi, Zn, Mg, Ca, Sn, Zr, Ti, etc. The metal heteroatom doped in the carbon layer becomes the nucleation center of LiF during the first film formation process, forming a uniform alkali metal fluoride salt in the SEI, which helps to form a thin and dense SEI film, improve the Young's modulus of the SEI film, inhibit irreversible lithium loss, and increase the cycle life of the battery. At the same time, it increases the ion migration rate, thereby improving the cycle stability of the lithium-ion battery under high current.

[0014] In the above technical solution, the weight ratio of the metal heteroatom to graphite is 0.5-5%, preferably 1-3%, which is conducive to the formation of uniform alkali metal fluoride salts during the initial SEI film formation process, helps to form a thin and dense SEI film, improves the Young's modulus of the SEI film, inhibits irreversible lithium loss, and increases the cycle life of the battery.

[0015] In the above technical solution, the graphite is any carbon-based negative electrode material such as natural graphite, artificial graphite, spherical graphite, etc.

[0016] In the second aspect, the present invention proposes a method for preparing a modified graphite negative electrode material for a lithium ion battery. This method is only used as an example, and other methods for preparing this material are also within the scope of protection of this patent, including the following steps:

[0017] Step 1, fully mixing a certain amount of graphite, an organic carbon source precursor containing two or more highly electronegative non-metallic heteroatoms such as N, O, and F, and one or more inorganic or organic salt precursors of metal heteroatoms with a solvent, and then evaporating and removing the solvent to obtain a solid powder;

[0018] Step 2, carbonizing the solid powder obtained in step 1 in nitrogen or argon inert gas at 300-700° C. for 0.5-5 h, and cooling to room temperature to obtain the desired negative electrode graphite composite material for the battery;

[0019] In the above technical scheme, in step 1, the non-metallic heteroatom organic carbon source precursor includes a nitrogen-containing organic carbon source (including but not limited to melamine, aniline, polyacrylonitrile, etc.), an oxygen-containing organic carbon source (including but not limited to pyrogallol, quercetin, kaempferol, gallic acid, catechin, tannic acid and polyphenolamide, pyrogallol, etc.), and a fluorine-containing organic carbon source (including but not limited to polytetrafluoroethylene, copolymers of vinylidene fluoride and chlorotrifluoroethylene, copolymers of vinylidene fluoride and hexafluoropropylene, terpolymers of vinylidene fluoride, chlorotrifluoroethylene and hexafluoropropylene, or derivatives of the above fluorine-containing polymers, etc.).

[0020] In the above technical solution, in step 1, the metal heteroatom inorganic and organic salt precursors include nitrates, sulfates, chlorides, acetates, etc. of metal ions such as Bi, Zn, Mg, Ca, Sn, Zr, and Ti.

[0021] In the above technical solution, in step 1, the solvent includes one or more of water, ethanol, acetone, dimethylformamide, tetrahydrofuran, etc. in different proportions, preferably a mixture of any proportions to dissolve the precursor and disperse the graphite.

[0022] In a third aspect, the present invention provides a negative electrode plate, comprising the negative electrode active material of the first aspect of the present invention.

[0023] In the above technical solution, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode film layer is formed by coating the negative electrode slurry as described above on the negative electrode current collector. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode film layer is arranged on any one or both of the two opposite surfaces of the negative electrode current collector.

[0024] In the above technical solution, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0025] In the above technical solution, the negative electrode sheet can be prepared in the following manner: the above components for preparing the negative electrode sheet, such as a binder, a conductive agent, the negative electrode active material described in the first aspect of the present invention and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after processes such as drying and cold pressing, the negative electrode sheet can be obtained.

[0026] In a fourth aspect, the present invention provides a secondary battery, comprising the negative electrode sheet of the embodiment of the third aspect of the present invention.

[0027] In a fifth aspect, the present invention provides an electrical device, comprising the secondary battery of the embodiment of the fourth aspect of the present invention.

[0028] Beneficial effects:

[0029] Compared with the existing process, the negative electrode material can form a more stable, dense, continuous and high-ionic conductivity fluoride-rich SEI film, which can effectively avoid the breakage and loss of the SEI film during the later charging and discharging process. While significantly improving the first-round coulomb efficiency of the negative electrode material, it can also significantly improve the cycle life and large current charging and discharging performance of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is a scanning electron microscope photo of natural graphite;

[0032] Figure 2 is a transmission electron microscope photograph of Example 1;

[0033] Figure 3 This is a scanning electron microscope photograph of Example 1;

[0034] Figure 4 This is a scanning electron microscope carbon spectrum scanning photograph of Example 1;

[0035] Figure 5 This is a scanning electron microscope zinc spectrum scanning photograph of Example 1;

[0036] Figure 6 This is a scanning electron microscope oxygen spectrum scanning photograph of Example 1;

[0037] Figure 7 This is a scanning electron microscope nitrogen spectrum scanning photograph of Example 1;

[0038] Figure 8 This is the XPS spectrum of the SEI film on the surface of the material after one cycle of charge and discharge at 0.1 C in Example 1;

[0039] Fig. 9 This is the XPS energy spectrum of the SEI film on the surface of the material in comparative example 3 after one cycle of charge and discharge at 0.1 C. DETAILED DESCRIPTION

[0040] Hereinafter, the embodiments of the binder, separator, pole piece, electrode assembly, battery cell, battery and electrical device of the present invention are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present invention and are not intended to limit the subject matter described in the claims.

[0041] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.

[0042] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.

[0043] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0044] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0045] If not specifically stated, in the present invention, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0046] Example 1

[0047] Mechanical mixing of raw materials: Commercially available natural graphite, melamine and gallic acid are fully mixed in a weight ratio of 100:6.5:13 and dissolved in ethanol, and then a certain amount of zinc acetate is added (the mass ratio of graphite to Zn is 100:2). After the mixture is fully stirred and mixed, the solvent is removed under vacuum stirring conditions at 120°C to obtain a solid mixture, and the solid mixture is heated to 500°C at a rate of 5°C / min under a nitrogen atmosphere, and kept warm for 2h to obtain a N,O-Zn co-doped carbon-coated natural graphite negative electrode material. The ratio of the doped carbon content of the obtained material to the graphite is X = ((M 样品 —M 石墨 ) / M 石墨 ). The N, O content was obtained by quantitative analysis using an element analyzer, and the metal content in the carbon material was obtained by inductively coupled plasma optical emission spectroscopy (ICP-OES). The results are listed in Table 1.

[0048] Example 2

[0049] The commercially available spherical graphite and pyrogallic acid and the terpolymer of vinylidene fluoride, chlorotrifluoroethylene and hexafluoropropylene were fully mixed in a weight ratio of 100: 1.3: 2 and dissolved and dispersed in acetone, and then a certain amount of calcium sulfate (the mass ratio of graphite to Ca was 100: 0.5) was added. After the mixture was fully stirred and mixed at 50 ° C, the solvent was removed under vacuum stirring conditions at 120 ° C to obtain a solid mixture, and the solid mixture was heated to 700 ° C at a heating rate of 5 ° C / min under a nitrogen atmosphere, and kept warm for 0.5 h to obtain an O, F-Ca co-doped carbon-coated natural graphite negative electrode material. The doped carbon content, O, F content, and metal content of the obtained material were tested in the same manner as in Example 1. The results are listed in Table 1.

[0050] Example 3

[0051] The commercially available artificial graphite and aniline and the terpolymer of vinylidene fluoride, chlorotrifluoroethylene and hexafluoropropylene were fully mixed in a weight ratio of 100: 13.5: 20, dissolved and dispersed in acetone, and then a certain amount of magnesium nitrate (the mass ratio of graphite to Mg was 100: 5) was added. After the mixture was fully stirred and mixed at 50°C, the solvent was removed under vacuum stirring conditions at 120°C to obtain a solid mixture, and the solid mixture was heated to 600°C at a heating rate of 5°C / min under a nitrogen atmosphere, and kept warm for 5h to obtain a N, F-Mg co-doped carbon-coated natural graphite negative electrode material. The doped carbon content, N, F content, and metal content of the obtained material were tested in the same manner as in Example 1. The results are listed in Table 1.

[0052] Example 4

[0053] The commercially available natural graphite, polyacrylonitrile and tannic acid were fully mixed in a weight ratio of 100: 13.5: 13.5, dissolved and dispersed in nitrogen-nitrogen dimethylformamide, and then a certain amount of bismuth nitrate was added (the mass ratio of graphite to Bi was 100: 3). After the mixture was fully stirred and mixed at 50 ° C, the solvent was removed under vacuum stirring conditions at 120 ° C to obtain a solid mixture, and the solid mixture was heated to 450 ° C at a heating rate of 5 ° C / min under a nitrogen atmosphere, and kept warm for 1 hour to obtain N, O-Bi co-doped carbon-coated natural graphite negative electrode material. The doped carbon content, N, O content, and metal content of the obtained material were tested in the same manner as in Example 1. The results are listed in Table 1.

[0054] Example 5

[0055] Commercially available natural graphite, polyacrylonitrile and pyrogallic acid were fully mixed in a weight ratio of 100: 13.5: 13.5, dissolved and dispersed in nitrogen-nitrogen dimethylformamide, and then a certain amount of tin acetate (the mass ratio of graphite to Sn was 100: 3) was added. After the mixture was fully stirred and mixed at 50°C, the solvent was removed under vacuum stirring conditions at 120°C to obtain a solid mixture, and the solid mixture was heated to 450°C at a heating rate of 5°C / min under a nitrogen atmosphere, and kept warm for 1h to obtain a N,O-Sn co-doped carbon-coated natural graphite negative electrode material. The doped carbon content, N, O content and metal content of the obtained material were tested in the same manner as in Example 1. The results are listed in Table 1.

[0056] Example 6

[0057] Commercially available natural graphite, melamine and catechin were fully mixed in a weight ratio of 100:13.5:13.5, dissolved and dispersed in ethanol, and then a certain amount of zirconium nitrate (the mass ratio of graphite to Zr was 100:3) was added. After the mixture was fully stirred and mixed at 50°C, the solvent was removed under vacuum stirring conditions at 120°C to obtain a solid mixture, and the solid mixture was heated to 450°C at a heating rate of 5°C / min under a nitrogen atmosphere, and kept warm for 2h to obtain a N,O-Zr co-doped carbon-coated natural graphite negative electrode material. The doped carbon content, N, O content and metal content of the obtained material were tested in the same manner as in Example 1. The results are listed in Table 1.

[0058] Example 7

[0059] Commercially available natural graphite, melamine and catechin were fully mixed in a weight ratio of 100: 13.5: 13.5, dissolved and dispersed in ethanol, and then a certain amount of titanium nitrate (the mass ratio of graphite to titanium was 100: 3) was added. After the mixture was fully stirred and mixed at 50°C, the solvent was removed under vacuum stirring conditions at 120°C to obtain a solid mixture, and the solid mixture was heated to 450°C at a heating rate of 5°C / min under a nitrogen atmosphere, and kept warm for 3h to obtain a N, O-Ti co-doped carbon-coated natural graphite negative electrode material. The doped carbon content, N, O content and metal content of the obtained material were tested in the same manner as in Example 1. The results are listed in Table 1.

[0060] Comparative Example 1

[0061] Commercially available natural graphite and melamine were fully mixed in a weight ratio of 100:20 and then dissolved and dispersed in ethanol. After the mixture was fully stirred and mixed, the solvent was removed under vacuum stirring conditions at 120°C to obtain a solid mixture. The solid mixture was heated to 500°C at a rate of 5°C / min under a nitrogen atmosphere and kept warm for 2h to obtain a N-doped carbon-coated natural graphite negative electrode material. The doped carbon content and N content test methods of the obtained material were the same as those in Example 1. The results are listed in Table 1.

[0062] Comparative Example 2

[0063] Commercially available natural graphite and gallic acid were fully mixed in a weight ratio of 100:20 and then dissolved and dispersed in ethanol. After the mixture was fully stirred and mixed, the solvent was removed under vacuum stirring at 120°C to obtain a solid mixture. The solid mixture was heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 2h to obtain an O-doped carbon-coated natural graphite negative electrode material. The doped carbon content and O content test methods of the obtained material were the same as those in Example 1. The results are listed in Table 1.

[0064] Comparative Example 3

[0065] Commercially available natural graphite, melamine and gallic acid were fully mixed in a weight ratio of 100:6.5:13 and dissolved in ethanol. After the mixture was fully stirred and mixed, the solvent was removed under vacuum stirring at 120°C to obtain a solid mixture. The solid mixture was heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 2h to obtain an O-doped carbon-coated natural graphite negative electrode material. The doped carbon content and N, O content test methods of the obtained material were the same as those in Example 1. The results are listed in Table 1.

[0066] Comparative Example 4

[0067] The commercially available natural graphite and melamine were fully mixed in a weight ratio of 100:20 and dissolved in ethanol, and then a certain amount of zinc acetate (the mass ratio of graphite to Zn was 100:2) was added, and after the mixture was fully stirred and mixed, the solvent was removed under vacuum stirring conditions at 120°C to obtain a solid mixture, and the solid mixture was heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere, and kept warm for 2h to obtain a N-Zn-doped carbon-coated natural graphite negative electrode material. The doped carbon content, N content test method and metal content test method of the obtained material are the same as those in Example 1. The results are listed in Table 1.

[0068] Comparative Example 5

[0069] The commercially available natural graphite and gallic acid were fully mixed in a weight ratio of 100:20 and dissolved in ethanol, and then a certain amount of zinc acetate (the mass ratio of graphite to Zn was 100:2) was added, and after the mixture was fully stirred and mixed, the solvent was removed under vacuum stirring conditions at 120°C to obtain a solid mixture, and the solid mixture was heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere, and kept warm for 2h to obtain an O-Zn doped carbon-coated natural graphite negative electrode material. The doped carbon content, O content test method and metal content test method of the obtained material are the same as those in Example 1. The results are listed in Table 1.

[0070] Performance Testing:

[0071] The modified graphite negative electrode materials in the embodiment and the comparative example were respectively subjected to the first round of coulombic efficiency test and high current charge and discharge performance test by the button half-cell method, and the cycle life test results by the soft pack full-cell method are listed in Table 2. The specific performance test conditions are as follows:

[0072] 1) Half-cell performance test:

[0073] (1) Assembly of half-cell

[0074] Preparation of electrode: At room temperature, the obtained negative electrode material: CMC: SP: SBR = 95%: 2%:

[0075] 1.5%:1.5% (mass ratio) mixed evenly in pure water to prepare slurry; apply the slurry evenly on the copper foil, with a coating surface density of about 4mg / cm 2 Then put the copper foil into a vacuum drying oven at 80℃ for 10 hours. Cut the dried copper foil into pieces with an area of ​​2cm 2 The disc is made into the working electrode.

[0076] Assembly of half-cell: At room temperature, use lithium metal sheet as the counter electrode, the product obtained in step 1 as the working electrode, PE diaphragm (polyethylene) as the diaphragm, 1 mol / L LiPF6 / EC:DEC (volume ratio of 1:1) solution as the electrolyte, and assemble into a CR2430 button cell in a vacuum glove box.

[0077] The assembled battery was left to stand at room temperature for 24 hours before starting the electrochemical test. The electrochemical performance test was carried out on an American Arbin BT2000 battery tester.

[0078] (2) Carry out capacity and first efficiency test, discharge at 0.1C to 0.005V, obtain the first lithium-inserted capacity of graphite, let it stand for 30 minutes, charge at 0.1C to 2.0V, complete the first cycle, obtain the first lithium-free capacity of graphite, which is the material capacity. The ratio of the first lithium-free capacity to the lithium-inserted capacity is the first efficiency.

[0079] (3) Room temperature 1C constant current SOC test method: At room temperature, on the Arbin BT2000 battery tester, the button half-cell that has completed the first cycle is discharged at a 1C constant current to 0.005V to obtain the corresponding material lithium embedded gram capacity. The ratio of this gram capacity to the lithium removed gram capacity of the first cycle material is the room temperature 1C constant current SOC.

[0080] (4) Room temperature 3C constant current SOC test method: At room temperature, on the Arbin BT2000 battery tester, the button half-cell that has completed the first cycle is discharged at 3C constant current to 0.005V to obtain the corresponding material lithium embedded gram capacity. The ratio of this gram capacity to the lithium removed gram capacity of the first cycle material is the room temperature 3C constant current SOC.

[0081] (5) Room temperature 5C constant current SOC test method: At room temperature, on the Arbin BT2000 battery tester, the button half-cell that has completed the first cycle is discharged at 5C constant current to 0.005V to obtain the corresponding material lithium embedded gram capacity. The ratio of this gram capacity to the lithium removed gram capacity of the first cycle material is the room temperature 5C constant current SOC.

[0082] 2) Full battery performance test:

[0083] (1) Assembly of soft-pack full battery

[0084] The negative electrode of the whole battery is: the obtained negative electrode material: SP: CMC: SBR = 95%: 2%: 1.5%: 1.5% (mass ratio), the positive electrode of the whole battery is LCO: PVDF: SP: KS-6 = 95%: 2%: 2%: 1% (mass ratio), the electrolyte of the whole battery is 1M-LiPF6 (EC: DMC: EMC) = 1: 1: 1 (volume ratio) solution, the positive electrode design capacity is 145mAh / g, the negative electrode design capacity is 360mAh / g, the design excess coefficient is 1.10, and the compaction density of the negative electrode material pole piece is 1.50g / cm 3 , single surface density is 10mg / cm 2 .

[0085] The electrochemical performance test was carried out on an American Arbin BT2000 battery tester.

[0086] (2) Cycle number test conditions are as follows: at 25°C and 45°C, the secondary battery is subjected to 1C / 1C cycle test with a charge and discharge voltage range of 2.88 to 4.35V. The test is stopped when the capacity decays to 80% of the initial discharge capacity. The cycle stability of the battery at 25°C and 45°C 1C is measured respectively.

[0087] Figure 1 The scanning electron microscope photo of natural graphite is given. Figure 2 and Figure 3 The transmission electron microscope photo and scanning electron microscope photo of the modified natural graphite in Example 1 are given. It can be seen from the figure that a uniform doped carbon coating layer can be formed on the surface of the natural graphite through the process of Example 1. Figure 4-Figure 7 The scanning electron microscope photographs of Example 1 and the energy spectra of C, Zn, N, and O are given. It can be seen that non-metallic and metallic heteroatoms such as N, O-Zn, etc. are uniformly doped in the carbon coating layer.

[0088] Figure 8 This is the XPS spectrum of the F element of the SEI film on the negative electrode surface obtained by disassembling the battery after one cycle of 0.1C charge and discharge under the button half-cell test conditions of Example 1. It can be seen from the figure that the co-doping structure of the synergistic effect of the highly electronegative N, O non-metallic heteroatoms and metal heteroatoms is conducive to the formation of a LiF-rich SEI film. At the same time, due to the uniform and dense doped carbon layer on the surface ( Figure 2 ,3), so the material not only has high first-round coulombic efficiency, but also has high capacity retention rate under large current charge and discharge conditions, and the cycle stability is also significantly improved. Comparative Example 3, which only contains high electronegativity N,O doped carbon materials, is not conducive to the deposition of LiF without adding metal, and the LiF content in the formed SEI film is low ( Fig. 9), so although the first-round coulombic efficiency of this material is relatively high, the unstable SEI film and the relatively low ion conductivity lead to significantly reduced cycle stability and capacity retention rate of this material under high-power charge and discharge conditions (see Table 2).

[0089] Table 1 and Table 2 list the ingredients, preparation process conditions and battery test performance of all embodiments and comparative examples respectively.

[0090] Table 1 Material composition and preparation process of the examples

[0091]

[0092] Table 2 Electrochemical performance test results of the examples

[0093]

[0094] Compared with Example 1, Comparative Examples 4 and 5 are natural graphites doped with carbon coated with single non-metallic heteroatoms, metal heteroatoms (N, Zn), (O, Zn), respectively. It can be seen from Table 2 that the electronegativity of the coated carbon surface has an important influence on improving the first-round coulomb efficiency and cycle stability of the material. Single high electronegativity non-metallic heteroatom doping cannot form an effective synergistic effect to increase the content of LiF in the SEI film. Therefore, a large amount of unstable organic SEI film will be formed during the SEI film formation process, thereby causing the first-round coulomb efficiency of the material to decrease, while the capacity retention rate and cycle stability of high current charge and discharge are significantly reduced. This result fully illustrates the necessity of at least two or more high electronegativity non-metallic heteroatoms and metal heteroatom doped carbon preparations to work synergistically.

[0095] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features invented herein.

Claims

1. A modified graphite negative electrode material for a lithium ion battery, characterized in that: The invention comprises an inner core and an outer shell, wherein the inner core is graphite, the outer shell is a carbon material co-doped with non-metallic heteroatoms and metal heteroatoms, the weight ratio of the doped carbon material to the graphite is X, 2%≦X≦20%; the non-metallic heteroatoms are any two or more of N, O, and F, the weight ratio of the non-metallic heteroatoms to the graphite is Y, 0.5%≦Y≦5%; the metal heteroatoms are any one or more of Bi, Zn, Mg, Ca, Sn, Zr, and Ti, the weight ratio of the metal heteroatoms to the graphite is Z, 0.5%≦Z≦5%.

2. A lithium ion battery modified graphite negative electrode material according to claim 1, characterized in that: 5%≦X≦15%。 3. A lithium ion battery modified graphite negative electrode material according to claim 1, characterized in that: 1%≦Y≦3%。 4. A lithium ion battery modified graphite negative electrode material according to claim 1, characterized in that: 1%≦Z≦3%。 5. A lithium ion battery modified graphite negative electrode material according to claim 1, characterized in that: The graphite is natural graphite or artificial graphite.

6. The method for preparing a lithium ion battery modified graphite negative electrode material according to claim 1, characterized in that: The steps include: Step 1, fully mixing graphite, an organic carbon source precursor of a non-metallic heteroatom, and an inorganic or organic salt precursor of a metal heteroatom with a solvent, and then evaporating the solvent to obtain a solid powder; Step 2: Carbonize the solid powder obtained in step 1 in nitrogen or argon at 300-700° C. for 0.5 h-5 h, and cool to room temperature to obtain a modified graphite negative electrode material for a lithium ion battery.

7. The method for preparing a modified graphite negative electrode material for a lithium ion battery according to claim 6, characterized in that: The non-metallic heteroatom organic carbon source precursor includes a nitrogen-containing organic carbon source, an oxygen-containing organic carbon source, or a fluorine-containing organic carbon source, and the metal heteroatom inorganic or organic salt precursor includes a nitrate, sulfate, chloride, or acetate of Bi, Zn, Mg, Ca, Sn, Zr, or Ti metal ions.

8. An application of modified graphite negative electrode material for lithium ion batteries, characterized in that: The modified graphite negative electrode material for lithium-ion batteries according to any one of claims 1 to 7 is used for a negative electrode plate, the negative electrode plate is used for a secondary battery, and the secondary battery is used for an electrical device.

Citation Information

Patent Citations

  • Boron-doped resin coated artificial graphite material

    CN112952095A

Cited By

  • Diatom shell doped material for strengthening performance of graphite as well as preparation method and application of diatom shell doped material

    CN121260753A